Concrete prepared based on tailing mud and preparation method and application thereof

CN118420271BActive Publication Date: 2026-10-16CHINA RESOURCES CEMENT TECH R & D (GUANGXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410522581.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-28
Publication Date
2026-10-16
Estimated Expiration
2044-04-28

AI Technical Summary

Benefits of technology

[0063] (1) The concrete provided by the present invention utilizes the tailings that are difficult to handle in the sand and gravel aggregate industry to partially replace the fly ash in the raw materials, and prepares commercial concrete that meets the national standards, thereby reducing the production cost of concrete, realizing the resource utilization of waste, and bringing good social and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004815564010000071
    Figure BDA0004815564010000071
  • Figure BDA0004815564010000072
    Figure BDA0004815564010000072
  • Figure BDA0004815564010000073
    Figure BDA0004815564010000073
Patent Text Reader

Abstract

The application discloses concrete prepared based on tailing mud and a preparation method and application thereof, and the concrete comprises the following raw materials in parts by mass: cement 120-160 parts, mineral powder 30-70 parts, fly ash 35-75 parts, machine-made sand 700-1000 parts, tailing mud 15-55 parts, aggregate 900-1200 parts and additive 7-9 parts. The concrete prepared based on tailing mud provided by the application improves the physical performance of the concrete, reduces the production cost, is convenient to operate and is relatively safe, so that the environmental protection risk and the safety risk of an enterprise are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically relating to a type of concrete prepared from tailings, its preparation method, and its application. Background Technology

[0002] Sand and gravel aggregates are the most widely used and irreplaceable building materials in infrastructure construction and the real estate industry, and the market demand for sand and gravel is expected to continue to grow. With the end of the era of traditional extensive and rapid expansion in the sand and gravel industry, the future development model of the industry will be very different from before. High-quality development will become the main theme and core task of the sand and gravel and equipment industry, while reduction, optimization, and intensive efficiency will be the future development direction of the sand and gravel industry.

[0003] Building a waste recycling system is an important measure for aggregate enterprises to implement a comprehensive conservation strategy, safeguard national resource security, actively and steadily promote carbon peaking and carbon neutrality, and accelerate the green transformation of development patterns. The recovery of fine sand and the treatment of tailings generated during the wet production process of manufactured sand and gravel are pressing problems for sand and gravel enterprises and are key to efficient resource utilization. In the wet production of sand and gravel aggregates, a large amount of slurry and tailings are inevitably generated. Current solutions generally involve separating the mud and water using a filter press, and then further processing the resulting mud cake, such as for preparing roadbed materials. However, this method is time-consuming and requires large equipment. The overall filter press process is lengthy and costly, making it difficult for current filter press capacity to match the massive amount of tailings generated. Summary of the Invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a type of concrete prepared from tailings, wherein the concrete is prepared by partially replacing fly ash with granite tailings, which improves the physical properties of the concrete, reduces production costs, is easy to operate, and has high safety, thereby reducing the environmental and safety risks for enterprises.

[0005] The present invention also proposes a method for preparing the above-mentioned concrete.

[0006] The present invention also proposes the application of the above-mentioned concrete.

[0007] According to a first aspect of the present invention, a concrete based on tailings is provided, the concrete comprising the following raw materials in parts by weight: 120-160 parts cement, 30-70 parts mineral powder, 35-75 parts fly ash, 700-1000 parts manufactured sand, 15-55 parts tailings, 900-1200 parts aggregate, and 7-9 parts admixture.

[0008] In some embodiments of the present invention, the concrete further includes 1 to 3 parts of an synergist and 1 to 5 parts of a water-reducing agent.

[0009] In some preferred embodiments of the present invention, the concrete further includes 1.2 to 2 parts of an synergist and 2 to 4 parts of a water-reducing agent.

[0010] In some preferred embodiments of the present invention, the concrete further includes 1.43 parts of an synergist and 3 parts of a water-reducing agent.

[0011] In some preferred embodiments of the present invention, the synergist includes triethanolamine.

[0012] In some preferred embodiments of the present invention, the water-reducing agent includes a polycarboxylate water-reducing agent.

[0013] In some embodiments of the present invention, the concrete comprises the following raw materials in parts by weight: 130-150 parts cement, 40-60 parts mineral powder, 36-72 parts fly ash, 800-900 parts manufactured sand, 18-54 parts tailings, 1000-1100 parts aggregate, and 8-9 parts admixture.

[0014] In some preferred embodiments of the present invention, the concrete comprises the following raw materials in parts by weight: 145 parts cement, 50 parts mineral powder, 60 parts fly ash, 850 parts manufactured sand, 30 parts tailings, 1050 parts aggregate, and 8.55 parts admixture.

[0015] In some embodiments of the present invention, the cement includes ordinary silicate cement.

[0016] In some preferred embodiments of the present invention, the average particle size of the cement is 20 to 40 μm.

[0017] In some more preferred embodiments of the present invention, the cement has an average particle size of 27 μm.

[0018] In some embodiments of the present invention, the mineral powder includes at least one of granulated blast furnace slag powder, limestone powder, coal gangue powder, and wollastonite powder.

[0019] In some preferred embodiments of the present invention, the mineral powder is granulated blast furnace slag powder.

[0020] In some preferred embodiments of the present invention, the specific surface area of ​​the mineral powder is 300-500 cm². 2 / g.

[0021] In some more preferred embodiments of the present invention, the specific surface area of ​​the mineral powder is 400 cm². 2 / g.

[0022] In some preferred embodiments of the present invention, the average particle size of the mineral powder is 0.4 to 0.6 mm.

[0023] In some preferred embodiments of the present invention, the average particle size of the mineral powder is 0.5 mm.

[0024] In some embodiments of the present invention, the average particle size of the fly ash is 0.05 to 0.2 mm.

[0025] In some preferred embodiments of the present invention, the average particle size of the fly ash is 0.1 mm.

[0026] In some embodiments of the present invention, the average particle size of the manufactured sand is 0.4 to 0.6 mm.

[0027] In some preferred embodiments of the present invention, the average particle size of the manufactured sand is 0.5 mm.

[0028] In some preferred embodiments of the present invention, the manufactured sand includes at least one of granite manufactured sand, basalt manufactured sand, limestone manufactured sand, and sandstone manufactured sand.

[0029] In some more preferred embodiments of the present invention, the manufactured sand is granite manufactured sand.

[0030] In some preferred embodiments of the present invention, the fineness modulus of the manufactured sand is 1.5 to 4.

[0031] In some more preferred embodiments of the present invention, the fineness modulus of the manufactured sand is 2 to 3.

[0032] In some more preferred embodiments of the present invention, the fineness modulus of the manufactured sand is 2.5.

[0033] In some preferred embodiments of the present invention, the MB value of the manufactured sand, as detected by the methylene blue method, is less than 1.3.

[0034] In some more preferred embodiments of the present invention, the MB value of the manufactured sand, as detected by the methylene blue method, is less than 1.2.

[0035] In some embodiments of the present invention, the tailings are obtained by further filtration of the product from the wet process of preparing manufactured sand using a filter press.

[0036] In some embodiments of the present invention, the average particle size of the tailings is 10–40 μm.

[0037] In some preferred embodiments of the present invention, the average particle size of the tailings is 20-30 μm.

[0038] In some preferred embodiments of the present invention, the average particle size of the tailings is 25 μm.

[0039] While manufactured sand and aggregates in concrete act as a framework for support, their dosage is limited and cannot be increased indefinitely. However, the addition of extremely fine tailings can effectively fill the gaps between the manufactured sand and aggregates, resulting in tight packing of the concrete components. Adding tailings is equivalent to indirectly increasing the cement content. Furthermore, the tailings reduce the overall cost of concrete. In addition, the tailings, a waste product from wet sand production, contain a small amount (approximately 0.5%) of polyacrylamide flocculant, which enhances the cohesion of materials in the concrete, thereby contributing to its strength.

[0040] In some embodiments of the present invention, the moisture content of the tailings is 10% to 20%.

[0041] In some preferred embodiments of the present invention, the moisture content of the tailings is 12% to 18%.

[0042] In some more preferred embodiments of the present invention, the moisture content of the tailings is 15%.

[0043] In some embodiments of the present invention, the average particle size of the aggregate is 10-30 mm.

[0044] In some preferred embodiments of the present invention, the average particle size of the aggregate is 15-25 mm.

[0045] In some more preferred embodiments of the present invention, the average particle size of the aggregate is 20 mm.

[0046] In some embodiments of the present invention, the aggregate includes granite aggregate.

[0047] In some embodiments of the present invention, the additive includes sodium gluconate.

[0048] In some embodiments of the present invention, the 3-day compressive strength of the concrete is 16.6 MPa.

[0049] In some embodiments of the present invention, the 7-day compressive strength of the concrete is 24.5 to 26 MPa.

[0050] In some preferred embodiments of the present invention, the 7-day compressive strength of the concrete is 25.1 MPa.

[0051] In some embodiments of the present invention, the 28-day compressive strength of the concrete is 38–45 MPa.

[0052] In some preferred embodiments of the present invention, the 28-day compressive strength of the concrete is 40-42 MPa.

[0053] In some preferred embodiments of the present invention, the 28-day compressive strength of the concrete is 41.3 MPa.

[0054] In some embodiments of the present invention, the water absorption rate of the concrete is 1% to 1.4%.

[0055] In some preferred embodiments of the invention, the water absorption rate of the concrete is 1.2%.

[0056] According to a second aspect of the present invention, a method for preparing concrete based on tailings as described in the first aspect of the present invention is provided, the method comprising the following steps:

[0057] Cement, mineral powder, fly ash, manufactured sand, tailings, aggregates, admixtures, synergists, water-reducing agents, and water are mixed evenly to obtain concrete based on tailings.

[0058] In some embodiments of the present invention, the water is 140 to 170 parts by mass.

[0059] In some preferred embodiments of the present invention, the water is 150 to 160 parts by mass.

[0060] In some more preferred embodiments of the present invention, the water is 156 parts by mass.

[0061] According to a third aspect of the present invention, the application of concrete as described in the first aspect of the present invention in the resource utilization of tailings is proposed.

[0062] The present invention has at least the following beneficial effects:

[0063] (1) The concrete provided by the present invention utilizes the tailings that are difficult to handle in the sand and gravel aggregate industry to partially replace the fly ash in the raw materials, and prepares commercial concrete that meets the national standards, thereby reducing the production cost of concrete, realizing the resource utilization of waste, and bringing good social and economic benefits.

[0064] (2) The concrete provided by the present invention improves the gradation of concrete materials and enhances the physical properties of concrete by incorporating tailings mud to replace fly ash. The process is simple, highly operable, and safe, and has certain promotional value.

[0065] (3) The concrete provided by the present invention applies the tailings that are difficult to dispose of in the aggregate industry to concrete materials, which can improve the tensile strength, toughness, permeability and durability of concrete materials, and improve the erosion resistance and service life of buildings, etc., and has a very broad application prospect.

[0066] 4) The concrete provided by this invention has a reasonable gradation gradient between the various materials. Based on the theory of close packing, the addition of extremely fine tailings can make the material packing more compact. In addition, it increases the amount of solid waste in the concrete, reduces production costs, and is in line with the green and low-carbon development trend of the building materials industry. Detailed Implementation

[0067] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0068] Materials and Definitions

[0069] In the following embodiments, the cement used is 42.5 ordinary Portland cement with an average particle size of 27 μm; the mineral powder used is granulated blast furnace slag powder with a specific surface area of ​​400 cm². 2 / g, average particle size is 0.5mm; the average particle size of the fly ash used is 0.1mm; the manufactured sand used is granite manufactured sand, with an average particle size of 0.5mm, a fineness modulus of 2.5, and an MB value less than 1.2 detected by the methylene blue method; the tailings used are products from the wet process of manufacturing sand preparation, which are then filtered by a filter press, with an average particle size of 25μm and a water content of 15%; the aggregate used is granite aggregate, with an average particle size of 20mm; the admixture used is sodium gluconate, purchased from Xinglong Chemical, with a purity of 98%; the synergist used is triethanolamine, purchased from Haiyuan Chemical, 99% stock solution; the water-reducing agent used is polycarboxylate water-reducing agent, purchased from Qimeng Chemical, with an active component >90%.

[0070] Example 1

[0071] This embodiment provides a concrete prepared from tailings, and also provides a method for preparing the concrete, which specifically includes the following steps:

[0072] Weigh out 145g of cement, 50g of mineral powder, 60g of fly ash, 850g of manufactured sand, 30g of tailings, 1050g of aggregate, 156g of water, 8.55g of admixture sodium gluconate, 1.43g of synergist triethanolamine, and 3g of polycarboxylate superplasticizer. Mix them to obtain concrete based on tailings.

[0073] Example 2

[0074] This embodiment provides a concrete prepared from tailings, and also provides a method for preparing the concrete, which specifically includes the following steps:

[0075] Weigh 145g of cement, 50g of mineral powder, 72g of fly ash, 850g of manufactured sand, 18g of tailings, 1050g of aggregate, 156g of water, 8.55g of admixture sodium gluconate, 1.43g of synergist triethanolamine, and 3g of polycarboxylate superplasticizer. Mix them to obtain concrete based on tailings.

[0076] Example 3

[0077] This embodiment provides a concrete prepared from tailings, and also provides a method for preparing the concrete, which specifically includes the following steps:

[0078] Weigh out 145g of cement, 50g of mineral powder, 48g of fly ash, 850g of manufactured sand, 42g of tailings, 1050g of aggregate, 156g of water, 8.55g of admixture sodium gluconate, 1.43g of synergist triethanolamine, and 3g of polycarboxylate superplasticizer. Mix them to obtain concrete based on tailings.

[0079] Example 4

[0080] This embodiment provides a concrete prepared from tailings, and also provides a method for preparing the concrete, which specifically includes the following steps:

[0081] Weigh out 145g of cement, 50g of mineral powder, 36g of fly ash, 850g of manufactured sand, 54g of tailings, 1050g of aggregate, 156g of water, 8.55g of admixture sodium gluconate, 1.43g of synergist triethanolamine, and 3g of polycarboxylate superplasticizer. Mix them to obtain concrete based on tailings.

[0082] Comparative Example 1

[0083] This comparative example provides a type of concrete and a method for preparing the concrete. The only difference between this method and the method provided in Example 1 is that 30g of tailings is replaced with 30g of fly ash, while the other raw materials and steps are the same.

[0084] Comparative Example 2

[0085] This comparative example provides a concrete prepared based on tailings, and also provides a method for preparing the concrete. The only difference between this method and the method provided in Example 1 is that the amount of fly ash is adjusted to 30g and the amount of tailings is adjusted to 60g, while the other raw materials and steps are the same.

[0086] Comparative Example 3

[0087] This comparative example provides a concrete prepared based on tailings, and also provides a method for preparing the concrete. The only difference between this method and the method provided in Example 1 is that 60g of fly ash is replaced with 60g of tailings. All other raw materials and steps are the same.

[0088] Test case

[0089] This experiment tested the slump, spread, compressive strength, and water absorption of concrete samples prepared in Examples 1-4 and Comparative Examples 1-3. The raw material formulations used in Examples 1-4 and Comparative Examples 1-3 are shown in Table 1. The above properties were tested in accordance with the national standard GB / T 50081-2019 Standard for Test Methods of Physical and Mechanical Properties of Concrete, and the results are shown in Tables 2 and 3.

[0090] Table 1. Raw material ratios (g) used in Examples 1-4 and Comparative Examples 1-3

[0091]

[0092] Table 2. Slump and spread test results of stirred samples (mm)

[0093]

[0094] Table 3. Test results of concrete compressive strength and water absorption.

[0095]

[0096]

[0097] As shown in Table 2, when the amount of tailings exceeds 10% of the cementitious system (the concrete system excluding aggregates, manufactured sand, and water), the slump and spread of the concrete samples gradually deteriorate until the concrete samples no longer slump or spread (Comparative Examples 2 and 3) as the amount of tailings increases and the amount of fly ash decreases. Slump and spread can characterize the fluidity of concrete. The reduced fluidity of the concrete prepared in Comparative Examples 2 and 3 is due to the fact that flocculants are often added during the tailings treatment process for dehydration and solidification. If too much tailings are added to the concrete, the flocculants contained therein will affect the fluidity of the concrete. Low fluidity will make it difficult to mix, transport, and pour the concrete. During the pouring process, defects such as honeycomb and pitting are also easily formed, which will ultimately affect the density and mechanical strength of the concrete. Therefore, the optimal amount of tailings in the concrete in this scheme is 10% of the cementitious system, and should be less than 20%.

[0098] As shown in Table 3, when no tailings are added to the concrete system (Comparative Example 1), its compressive strength is lower than that of the concrete with added tailings (Example 1 and Comparative Example 2). This is because the particle size of tailings is smaller than that of other raw material components. Therefore, concrete with added tailings is more likely to form a dense packing during mixing, further reducing porosity, thereby improving the mechanical strength of the concrete and reducing water absorption. Adding an appropriate amount of tailings can also improve the bonding between aggregates and cement paste, thereby improving the mechanical strength of the concrete. The compressive strength of the concrete obtained in Comparative Example 2 is lower than that in Example 1 because the fluidity of the concrete obtained in Comparative Example 2 is lower than that in Example 1. During the molding process, this leads to irregular shape of the concrete and damage to its structural integrity, thus affecting its mechanical properties. Therefore, the amount of tailings in the concrete formula provided by this invention should be less than 20% of the cementitious system.

[0099] The tailings sludge provided by this invention can partially replace fly ash in the resource-based disposal of concrete, reducing concrete production costs. The concrete and its preparation method provided by this invention can be used by building material enterprises to co-dispose of granite tailings sludge, alleviating the environmental pressure on aggregate enterprises while reducing concrete production costs for building material enterprises, thus possessing significant practical application value.

[0100] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.

Claims

1. A type of concrete prepared from tailings, characterized in that, The concrete comprises the following raw materials in parts by weight: 120-160 parts cement, 30-70 parts mineral powder, 35-75 parts fly ash, 700-1000 parts manufactured sand, 15-55 parts tailings, 900-1200 parts aggregate, and 7-9 parts admixture. The tailings are obtained by further filtration of the product from the wet process of preparing manufactured sand using a filter press, and the average particle size of the tailings is 10~40 μm. The manufactured sand includes at least one of granite manufactured sand, basalt manufactured sand, limestone manufactured sand and sandstone manufactured sand, and the average particle size of the manufactured sand is 0.4~0.6 mm; The aggregate is granite aggregate, and the average particle size of the aggregate is 10~30 mm.

2. The concrete according to claim 1, characterized in that, The concrete also includes 1-3 parts of an synergist and 1-5 parts of a water-reducing agent.

3. The concrete according to claim 2, characterized in that, The synergist includes triethanolamine.

4. The concrete according to claim 2, characterized in that, The water-reducing agent includes a polycarboxylate water-reducing agent.

5. The concrete according to claim 1, characterized in that, The cement includes ordinary Portland cement.

6. The concrete according to claim 1, characterized in that, The average particle size of the cement is 20~40 μm.

7. The concrete according to claim 1, characterized in that, The mineral powder includes at least one of granulated blast furnace slag powder, limestone powder, coal gangue powder, and wollastonite powder.

8. The concrete according to claim 1, characterized in that, The specific surface area of ​​the mineral powder is 300~500 cm². 2 / g.

9. The concrete according to claim 1, characterized in that, The average particle size of the mineral powder is 0.4~0.6 mm.

10. The concrete according to claim 1, characterized in that, The average particle size of the fly ash is 0.05~0.2mm.

11. The concrete according to claim 1, characterized in that, The fineness modulus of the manufactured sand is 1.5~4.

12. The concrete according to claim 1, characterized in that, The tailings have a moisture content of 10% to 20%.

13. The concrete according to claim 1, characterized in that, The additive includes sodium gluconate.

14. A method for preparing concrete based on tailings as described in any one of claims 1 to 13, characterized in that, The preparation method includes the following steps: Cement, mineral powder, fly ash, manufactured sand, tailings, aggregates, admixtures, synergists, water-reducing agents, and water are mixed evenly to obtain concrete based on tailings.

15. The application of concrete as described in any one of claims 1 to 13 in the resource utilization of tailings.